Report on Proceedings of the Sixth Annual Meeting of the European CME Forum, London, UK, 14–15 November 2013. Issue 1 (1st January 2014) - Murray, Ron
Abstract : Delegates from around the world attended the sixth annual meeting of the European CME Forum in London between 14 and 15 November 2013. The participants discussed best practices in continuing medical education and continuing professional development (CME–CPD) delivery, reviewed CME provision by various medical specialist societies, and viewed examples of e-CME educational activities in CME–CPD. The details of a new code for disclosure by European pharmaceutical companies were unveiled, and the implications were discussed with expert panels comparing the CME landscape in the United States with that in Europe. Accreditation systems were compared, and a number of informal sessions allowed the delegates to consider issues relevant to physician learners, transparency and accountability in CME planning and implementation, and opportunities for collaboration.